Violent minds : modernism and the criminal - Levay, Matthew (Cambridge University Press, 2019)
Just as cultural attitudes toward criminality were undergoing profound shifts in the late nineteenth and early twentieth centuries, modernist authors became fascinated by crime and its perpetrators, as well as the burgeoning genre of crime fiction. Throughout the period, a diverse range of British and American novelists took the criminal as a case study for experimenting with forms of psychological representation while also drawing on the conventions of crime fiction in order to imagine new ways of conceptualizing the criminal mind. Matthew Levay traces the history of that attention to criminal psychology in modernist fiction, placing understudied authors like Wyndham Lewis, Dorothy Sayers, Graham Greene, and Patricia Highsmith in dialogue with more canonical contemporaries like Joseph Conrad, Henry James, Dashiell Hammett, and Gertrude Stein. Levay demonstrates criminality's pivotal role in establishing quintessentially modernist forms of psychological representation and brings to light modernism's deep but understudied connections to popular literature, especially crime fiction.
Keywords: Crime in literature.; Criminals in literature.; Modernism (Literature) -- England.; Modernism (Literature) -- United States.; English fiction -- 19th century -- History and criticism.; English fiction -- 20th century -- History and criticism.; American fiction -- 19th century -- History and criticism.; American fiction -- 20th century -- History and criticism.; Criminalité dans la littérature.; Criminels dans la littérature.; Modernisme (Littérature) -- Angleterre.; Modernisme (Littérature) -- États-Unis.; Roman anglais -- 19e siècle -- Histoire et critique.; Roman anglais -- 20e siècle -- Histoire et critique.; Roman américain -- 19e siècle -- Histoire et critique.; Roman américain -- 20e siècle -- Histoire et critique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; American fiction; Crime in literature; Criminals in literature; English fiction; Modernism (Literature); England; United States; 1800-1999; Criticism, interpretation, etc.